Estimation of Range of Intraocular Pressure in Normal Individuals by Air Puff Tonometer - Ahmad Zeeshan Jamil, Zulfiqar Ali, Sarfraz Ahmad Mukhtar (Pakistan Journal of Ophthalmology, 2014)
Purpose: To estimate the range of IOP among normal individuals of different age groups. Material and Methods: This cross sectional descriptive study was conducted in Department of Ophthalmology, Bahawal Victoria hospital, Bahawalpur for a period of six months from 1st Feb 2010 to 31st July 2010. Data was collected from 300 normal individuals. The IOP was measured with air puff tonometer and Results were recorded on specially designed structured proforma. As the variable was quantitative in nature simple descriptive analysis was performed to calculate mean and range of intraocular pressure. Results: Mean IOP was found to be 15.368 ± 3.37 mm Hg giving a range of 5 to 25 mm Hg. No significant difference was found in the range of IOP between individuals of both sexes of various age groups. It also revealed that IOP in both eyes of the same individual was almost the same. Conclusion: In different age groups IOP was similar. Similarly, mean IOP was found to be same in two sexes. No difference was found in the IOP of two eyes. Key words: Intraocular pressure, air puff tonometer, glaucoma.